'Its all part of the big CHANGE': a grounded theory study of women's identity during menopause. (3rd July 2017) - Sergeant, Judith; Rizq, Rosemary
Abstract: This study explores the impact of menopause on women's identity and considers the effect of sociocultural factors on their experience of this stage of life. Semi-structured interviews were conducted with 11 women and analysed following constructivist Grounded Theory methods. Women described uncertainty produced by their changing bodies. Menopause was interpreted as marking transition to another phase of life, which necessitated renegotiation of role and status in the face of menopause narratives questioning women's relevance, vigour, attractiveness and emotional stability. We discuss results with reference to what appears to be an unspoken social "rule" keeping menopause hidden, something that enables dismissive menopausal narratives to persist. Our study suggests this resulted in some sense of emotional strain for participants as they negotiated a continuing narrative of their lives through a period of change. However, results also indicate that menopause may provide an opportunity for women to refocus on their goals and wellbeing. We conclude by considering the implications of the study for healthcare professionals working with menopausal women.